IMPLEMENTATION OF HORENSO AS SELF-MANAGEMENT FOR STUDENTS OF SMK WIDYA PRAJA UNGARAN - Handayani, Umi; Priventa, Hendrike; Riani, Rosalina Wahyu; Hanutama, Pinayung Aluka (Philosophica: Jurnal Bahasa, Sastra, dan Budaya, 2024)
Horenso culture is applied by all Japanese companies. In the division of the word horenso, it consists of 3 syllables, namely Houkoku which means to report, renraku which means to inform, soudan which means to consult. Horenso is a Japanese work culture in communication. Horenso culture itself, not only can be applied in the scope of the company, but in organizations on a smaller scale (class) can be applied. The purpose of this study is to determine the Implementation of Self-Management of Vocational School Widya Praja Ungaran Students in the concept of horenso and Describe theobstacles faced by students. This research applied descriptive qualitative method. The techniques used in data collection in this study were interviews, observation, documentation and triangulation. The results of this study are 26 students of SMK Widya Praja Ungaran, Multimedia Expertise Department who have implemented communication with the concept of horenso as a form of student self-management both to close friends, class leaders and homerooms. Students reported (houkoku) information to their close friends as much as 58%, reported to the class leader as much as 27%, and to the homeroom as much as 15%.Things that become obstacles for students when implementing horenso are as follows: not confident, embarrassed, afraid, consider information that is not important to convey, feeling lazy and students lack motivation.